2016
DOI: 10.1515/ap-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and prevalence of feline hemotropic mycoplasmas in Istanbul, Turkey

Abstract: The aim of this study was to investigate Mycoplasma spp. species in blood samples of the domestic cats from the province of Istanbul, Turkey. Three hundred eighty four blood samples of client-owned cats were used for the identification of Mycoplasma haemofelis (Mhf), Candidatus Mycoplasma haemominutum (CMhm) and Candidatus Mycoplasma turicensis (CMt) by Polymerase Chain Reaction (PCR) and Restriction Fragment Length Polymorphism (RFLP) assays. Out of 384 blood samples, 74 (19.3%) were positive for one of Mycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Hemoplasmosis was previously reported from different parts of the world (7,29,30,(35)(36)(37)(38)(39)(40). In the present study, Mycoplasma spp.…”
Section: Discussionsupporting
confidence: 65%
“…Hemoplasmosis was previously reported from different parts of the world (7,29,30,(35)(36)(37)(38)(39)(40). In the present study, Mycoplasma spp.…”
Section: Discussionsupporting
confidence: 65%
“…The first local case in the country was detected in 1991 in Istanbul [ 109 ]. The prevalence of hemotropic Mycoplasma in cats was 7.7% in Bursa, 17.5% in Izmir, 17.5% in Antalya, 30.8% in Ankara, 95% in Kayseri, 14.9% in Van, and 19.3% in Istanbul [ 110 , 111 ]. The DNA of this pathogen was detected in 30% of domestic cats in Spain [ 6 ], 17.2% in Serbia [ 112 ], 21.6% in Romania [ 113 ], 31% in New Zealand [ 114 ], 26% in Cyprus [ 46 ], and 13.2% in Italy [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have been conducted in the following years, most of them are case reports (Kurtdede & Ural, 2004;Ural et al, 2008;Aslan et al, 2010;Aslan et al, 2015). Therefore, the number of studies examining the prevalence of the disease is very limited (Akkan et al, 2005;Ural et al, 2009;Atalay et al, 2015;Cetinkaya et al, 2016). Ural et al, found the overall prevalence of the disease as 18.9% by PCR method in samples they collected from four different cities (Bursa, I…”
Section: Discussionmentioning
confidence: 99%
“…Grindem et al (1990) determined that many different factors such as FeLV infection, anaemia, bite abscesses are the risk factors for Mycoplasma infection but not the breed (Atalay et al, 2015). Although in some studies conducted in Turkey, searchers used the cats of different breeds, there is no result about the susceptibility of these breeds to infection (Ural et al, 2009;Atalay et al, 2015;Cetinkaya et al, 2016). Cats of the same breed are constantly mated with each other so that their characteristics are not lost in cats, and kittens are born without genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation